Higher Education and Global Social Injustice - Viggiano, Tiffany (2020)
This dissertation, composed of three unique scholarly articles, explores some of the ways in which institutions of higher education facilitate and mitigate social injustice on a global scale. Specifically analyzing the behavior of administrative actors—defined as those that serve in a leadership role outside of the classroom—the purpose of the research was twofold. Firstly, I aimed to identify the mechanisms by which administrative actors at U.S. and Finnish institutions of higher education legitimized and rationalized their involvement in globally unjust educational practices. Secondly, I sought to identify the ways in which administrative actors in these economically privileged countries can or have mitigated their institutions’ involvement in global structural injustice. Three lines of inquiry guided this investigation: (1) In what ways do administrative actors at U. S. and Finnish institutions of higher education justify and reproduce global injustice? (2) How might administrative actors at institutions of higher education in these economically affluent countries begin to mitigate their institutions’ role in global social injustice? (3) In what ways have administrative actors at institutions of higher education in these economically affluent countries addressed global social injustice? What challenges do they face? Sub-study I explained the ways in which 26 practitioners at community colleges in three different community colleges, located within different states the U.S., conceptualized the role of international students on their campuses. Findings indicated that administrative actors assumed international students to be a privileged class of students, and therefore did not apply the logic of social justice to the non-domestic students in the same way that it was applied to domestic counterparts. Through literature review, Sub-study II theoretically explored the ways in which humanism and critical theory have been applied to justify study abroad at the community college. Drawing on Young’s (2006) justice theory, Sub-study II constructs a globally critical humanist rationale to study abroad at the community college, and provides examples of the ways in which administrative actors could employ such a frame to advocate for more globally socially just practices. Sub-study III analyzed 15 interviews from administrative actors at an institution of higher education in Finland. Findings indicated that, although participants often articulated a responsibility for injustice, factors associated with neoliberalism, as well as unclear and conflicting definitions of global responsibility, contributed to blame shifting and excusing discourse. The investigation concludes with implications for future research.